ANALYSIS OF METHODS FOR SOLVING PROBLEMS OF RELIABILITY INDICATORS ASSESSMENT UNDER CONDITIONS OF A PRIORI UNCERTAINTY - KONONOVA, IRYNA; SUBACH, IHOR; ROMANENKO, VADYM; MOHYLEVYCH, VADYM (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The relevance of the study is due to the need to improve the reliability of electronic communication facilities and the quality of their maintenance and repair under conditions of a priori uncertainty. Modern electronic communication systems are complex technical complexes, the uninterrupted operation of which affects the quality of communication and information exchange. The use of approaches that take into account failures with time redundancy allows to expand the possibilities of assessing and predicting the reliability of electronic equipment, which is important for ensuring the stable functioning of the information and communication infrastructure. The article reveals the fundamental concepts of reliability of technical systems and establishes that a system with time redundancy has special characteristics that affect the definition of failure criteria and the assessment of its reliability. The analysis shows that in such systems, a failure does not necessarily lead to a disruption of functioning, since mechanisms are provided to restore performance within the permissible reserve time. Thus, to assess the reliability of such systems, it is advisable to use the concepts of “probability of failure-free operation” and “probability of disruption of operation”. The article presents single and complex indicators of reliability of systems with time redundancy and determines that single indicators, such as probability of failure-free functioning, failure rate and average time between failures, allow to evaluate individual properties of the system. At the same time, complex indicators, such as the availability factor and the operational readiness factor, make it possible to assess the efficiency of the system, taking into account time reserves and the process of restoring performance. Particular attention is paid to the impact of maintenance and repair on system reliability. It is determined that the quality of these activities directly affects the operational reliability of the facility, and their effectiveness is assessed by the technical utilization rate.